Penyuluhan Sertifikasi Halal untuk UMKM Berbasis Pariwisata di Era Digital: Inisiatif Keterlibatan Komunitas Internasional di Bukit Lawang, Indonesia: Halal Certification Education for Tourism-Based MSMEs in the Digital Era: An International Community Engagement Initiative in Bukit Lawang, Indonesia - Ilka Zufria; Zulham; Zalina Zakaria; Suhardi; M. Ridwan; Nurhanifah; Achyar Zein; Tisna Handayani; Rita Novita Sari; Muhammad Siddik Hasibuan (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Halal certification is important for improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), especially in tourism destinations attracting Muslim travelers. However, many business owners in Bukit Lawang still have limited understanding of halal certification requirements and digital certification procedures. This community engagement program provided practical education on halal certification and introduced participants to digital-based certification services. Activities included presentations, interactive discussions, and question-and-answer sessions involving 32 tourism-based MSME owners in Bukit Lawang, North Sumatra, organized through international collaboration between the Faculty of Science and Technology, Universitas Islam Negeri Sumatera Utara, Indonesia, and Universiti Malaya, Malaysia. Participants showed strong enthusiasm, gaining better understanding of halal principles, certification procedures, and digital platforms, while recognizing the strategic value of halal certification in enhancing consumer confidence, expanding market opportunities, and improving competitiveness. A satisfaction survey completed by 15 of the 32 participants showed consistently high mean scores (3.73–4.00 on a 1–4 scale) across all evaluated aspects, and all respondents expressed interest in future similar programs. These findings suggest that community-based educational programs can support the sustainable development of tourism-based MSMEs in the digital era.